Spatiotemporal mortality and demographic trends in a small cetacean: Strandings to inform conservation management. (September 2020) - IJsseldijk, Lonneke L.; ten Doeschate, Mariel T.I.; Brownlow, Andrew; Davison, Nicholas J.; Deaville, Rob; Galatius, Anders; Gilles, Anita; Haelters, Jan; Jepson, Paul D.; Keijl, Guido O.; Kinze, Carl Chr.; Olsen, Morten Tange; et al.
Abstract: With global increases in anthropogenic pressures on wildlife populations comes a responsibility to manage them effectively. The assessment of marine ecosystem health is challenging and often relies on monitoring indicator species, such as cetaceans. Most cetaceans are however highly mobile and spend the majority of their time hidden from direct view, resulting in uncertainty on even the most basic population metrics. Here, we discuss the value of long-term and internationally combined stranding records as a valuable source of information on the demographic and mortality trends of the harbour porpoise ( Phocoena phocoena ) in the North Sea. We analysed stranding records ( n  = 16, 181) from 1990 to 2017 and demonstrate a strong heterogeneous seasonal pattern of strandings throughout the North Sea, indicative of season-specific distribution or habitat use, and season-specific mortality. The annual incidence of strandings has increased since 1990, with a notable steeper rise particularly in the southern North Sea since 2005. A high density of neonatal strandings occurred specifically in the eastern North Sea, indicative of areas important for calving, and large numbers of juvenile males stranded in the southern parts, indicative of a population sink or reflecting higher male dispersion. These findings highlight the power of stranding records to detect potentially vulnerable population groups in time and space. This knowledge is vital for managers and can guide, for example, conservation measures such as the establishment of time-area-specific limits to potentially harmful human activities, aiming to reduce the number and intensity of human-wildlife conflicts. Highlights: International data synthesis to understand wildlife mortality and demographic trends We demonstrate the value of long-term surveillance exemplified by stranding records. Our analyses indicate potential vulnerable population groups in time and space. Analytical methods allow establishment of robust baseline of spatiotemporal variation. Results guide conservation measures aiming to reduce human-wildlife conflicts at sea.